Konflik Budaya Lokal Pada Masyarakat di Pulau Flores (Sebuah Analisis Komunikasi Lintas Budaya) - Jonas Klemens Gregorius Dori Gobang (Jurnal Komunikasi, 2014)
Cultural conflict can occur anywhere, let alone in a place where there are fundamental differences about the culture and society supporting a culture. Local cultural conflicts in society can be triggered by various factors both in ideological and practical level. This cultural conflict can be transformed into something that benefits society supporting different cultures when it can be properly managed through the appropriate approach. This study tries to present some aspects of cross-cultural communication theory approach in scrutinizing the conflict and manage cross-cultural conflict can be a potential conflict in order to establish brotherhood and unity in the diversity of cultures that exist on the island of Flores. This study can be used as a reference to see various forms of cultural conflict found in other cultures in various places.